A Study Analysis of Madura Folktale, Megaremeng in the Moral Values for Children Literature at SDIT Al Uswah Pamekasan - Ussilah Ussilah; Fabiola D. Kurnia; Eka Fadilah (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the moral values of Megaremeng of Madura tales in relation to children's attitudes. The descriptive qualitative approach was used in this study. The moral value of Imron Wakhid Harits’ Madura tale Megaremang, written in 2020, is the subject of this study. The findings revealed that Madura Folktales Megaremang, written in 2020 by Imron Wakhid Harits, reflected the moral values of SDIT Al Uswah Pamekasan students in the following ways: First, there were the moral values of education to consider: always helping, perseverance, and responsibility. Second, social education has a value in terms of humanity, concern, and empathy. Third, there was the value of cultural education in terms of mutual cooperation, adherence to rules, and mutual respect. The Megaremang folklore book is recommended as an alternative to literature in elementary schools because it fosters an appreciation for local culture in children, particularly those from the Madura region. Other researchers are encouraged to choose other books that relate to culture from a literary perspective to foster a generation of readers. Knowledge gained from this study may be used by other researchers examining literary works from an extrinsic perspective.